2003
DOI: 10.1103/physrevb.67.014531
|View full text |Cite
|
Sign up to set email alerts
|

Flux transitions in a superconducting ring

Abstract: We consider a superconducting ring embedded in a magnetic field. The magnetic field is initially too high to support a superconducting state, but is ideally slowly decreased and then reversed. During this process, the number of fluxoids trapped by the ring exhibits a complex pattern of transitions, which depends qualitatively on the ratios of the geometric dimensions of the ring to the coherence length. We evaluate the current around the ring and find rough agreement with experiments. However, we also predict … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…We find that the corresponding result is somewhat higher and broader than our jointly resummed curve. We can compare this curve to previous analyses in the literature [9,15,16]. It turns out that our "pure-Q T " resummed result is about 30% higher (in the peak of the distribution) than the one of the Resbos [15] code, and about 20% higher than the result of [16].…”
Section: Predictions For the Resummed Higgs Cross Sectionsupporting
confidence: 64%
See 1 more Smart Citation
“…We find that the corresponding result is somewhat higher and broader than our jointly resummed curve. We can compare this curve to previous analyses in the literature [9,15,16]. It turns out that our "pure-Q T " resummed result is about 30% higher (in the peak of the distribution) than the one of the Resbos [15] code, and about 20% higher than the result of [16].…”
Section: Predictions For the Resummed Higgs Cross Sectionsupporting
confidence: 64%
“…A new analysis for threshold resummation, including the recently calculated [4] next-to-next-to-leading logarithmic (NNLL) coefficients C (2) and D (2) , can be found in [13,14]. The resummed Higgs-Q T distribution has also recently been reinvestigated in [15,16,17], using the NNLL B (2) coefficient calculated in [18,19], and in [17] matched to the Higgs cross section at fixed Q T at NLO [20]. A complete understanding of soft gluon effects in differential distributions also requires a study of the relation between the two sets of corrections.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment has lead to a recent growing interest in the mechanism of flux transition in superconducting loops. 13,28,29 Multiple flux jumps and irreversible behavior of the magnetization were observed in thin mesoscopic rings by Vodolazov et al 30 At low magnetic field and for rings with sufficiently large radii, they showed experimentally and theoretically, using the time-dependent GL theory, that the vorticity may change by values larger than 1.…”
Section: Introductionmentioning
confidence: 98%
“…Fewer studies have focused on investigating fluxoid dynamics and phase slip rates [8][9][10]17]. Theoretical studies have addressed fluxoid dynamics as a function of ring geometry and magnetic field [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%